Knowledge and perception of integrity among Penang civil servants - Ismail, Rusnah; Ngah, Nazlin Emieza; Abdullah, Iskandar Hasan Tan; Mat Zin, Sakinah; Ibrahim, Norlaila; Ahmad Tajuddin, Nur Hafizah; Jusoff, Kamaruzaman; Salleh, Asri (IDOSI Publications, 2011)
The integrity of the civil servants needs to be greatly improved in order to turn Malaysian Vision 2020 into a reality. This objective of this research was to determine the level of awareness, knowledge and understanding on noble values particularly integrity among selected civil servants in selected State Government agencies in Pulau Pinang, Malaysia. The respondents were selected based on a purposive sampling technique. The research used a quantitative approach where self-administered structured questions were distributed. Descriptive and inference analysis were carried out to meet the research objectives outlined. The research findings showed that there were civil servants groups who were unclear and uncertain about the meaning of integrity in public sector. Those with shorter length of services were found to be less knowledgeable on the rule and procedure which led to them being unsure about integrity. Length of service was found to be inversely related to the perception on the knowledge of integrity, corruption and quality of service delivery. In this research, respondents might or might have not disclosed the actual truth when answering questions. Most heads of departments might have not wanted to disclose actual work realities of their offices. They, in particular, did not want to wash their dirty linen in public. For that reason, future research may improve on such limitation.